2013
DOI: 10.1593/neo.13314
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sarcosine Metabolism in Prostate Cancer Progression

Abstract: Metabolomic profiling of prostate cancer (PCa) progression identified markedly elevated levels of sarcosine (N-methyl glycine) in metastatic PCa and modest but significant elevation of the metabolite in PCa urine. Here, we examine the role of key enzymes associated with sarcosine metabolism in PCa progression. Consistent with our earlier report, sarcosine levels were significantly elevated in PCa urine sediments compared to controls, with a modest area under the receiver operating characteristic curve of 0.71.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 29 publications
10
134
2
1
Order By: Relevance
“…Chen et al [20] showed that expression of the tumor suppressor TMEFF2 reduced sarcosine levels in a model of aggressive prostate cancer and Dahl et al [21] showed that addition of exogenous sarcosine induced HER2/neu expression in androgendependent prostate cancer cells. Recently, Khan et al [22] have recapitulated the earlier findings that sarcosine in post-DRE urine sediments is a biomarker of prostate cancer, that the enzymes that produce and catabolize sarcosine are dysregulated in aggressive prostate cancer, and finally that modulation of the sarcosine metabolic pathway results in concordant modulation of prostate cancer aggressiveness, both in vitro and in animal models.…”
Section: Introductionmentioning
confidence: 82%
“…Chen et al [20] showed that expression of the tumor suppressor TMEFF2 reduced sarcosine levels in a model of aggressive prostate cancer and Dahl et al [21] showed that addition of exogenous sarcosine induced HER2/neu expression in androgendependent prostate cancer cells. Recently, Khan et al [22] have recapitulated the earlier findings that sarcosine in post-DRE urine sediments is a biomarker of prostate cancer, that the enzymes that produce and catabolize sarcosine are dysregulated in aggressive prostate cancer, and finally that modulation of the sarcosine metabolic pathway results in concordant modulation of prostate cancer aggressiveness, both in vitro and in animal models.…”
Section: Introductionmentioning
confidence: 82%
“…probability to suffer from non-aggressive prostate carcinoma with a lower ability to produce sarcosine due to dysregulation of the enzymes producing and catabolizing sarcosine (57). The current hypothesis is that most aged men have prostate cancer, and they have cells in their prostates that if observed on a needle biopsy would be diagnosed as prostate cancer (58).…”
Section: Cancer Patients Healthy Controls ---------------------------mentioning
confidence: 99%
“…We considered 11 C-sarcosine for prostate cancer imaging because metabolomic data indicated strongly elevated tissue levels in localized prostate cancer, particularly in metastatic disease (3). Also, the mere addition of sarcosine to cultured benign prostate epithelial cells induced an invasive phenotype (4). Although the sarcosine metabolism is well-characterized, its metabolic functions in the human body are still poorly understood and are currently under active investigation (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sarcosine levels have also been shown to increase during prostate cancer progression to metastatic disease (3), and knockdown of glycine-N-methyltransferase-the enzyme that generates sarcosine from glycine-attenuates prostate cancer invasion. The addition of exogenous sarcosine, or knockdown of the mitochondrial enzyme that leads to sarcosine degradation (sarcosine dehydrogenase [SARDH]), induces an invasive phenotype in benign prostate epithelial cells (4). Furthermore, there is evidence for a strong sarcosine-related induction of genes involved particularly in cell cycle progression (5).…”
mentioning
confidence: 99%